QBEND10 for the diagnosis of myelodysplastic syndromes in routinely processed bone marrow biopsy specimens. Issue 4 (April 1995) - Horny, H P; Wehrmann, M; Schlicker, H U; Eichstaedt, A; Clemens, M R; Kaiserling, E
Abstract : AIM–The assessment of the value of the antibody QBEND10, which is directed against the haemopoietic stem cell related antigen CD34, in the immunohistochemical diagnosis of myelodysplastic syndrome in routinely processed bone marrow biopsy specimens. METHODS–581 formalin fixed, paraffin embedded trephine biopsy specimens of the iliac crest were immunostained with QBEND10 (avidin-biotin complex/ABC method). The number of CD34+ haemopoietic stem cells/blast cells (referred to hereafter as CD34+ cells) was determined in each case. The Wilcoxon test was used for statistical analysis. RESULTS–The following diagnostic categories were defined: (1) normal or reactive bone marrow (n = 356), (2) lymphoproliferative disorders, usually non-Hodgkin's lymphoma of low grade malignancy or multiple myeloma (n = 118), (3) myelodysplastic syndrome (n = 22), (4) acute leukaemia (n = 44), and (5) myeloproliferative diseases (n = 41). The average number of CD34+ cells was very low (0.2/HPF) in normal and reactive bone marrow, in lymphoproliferative disorders and in the myelodysplastic syndrome subtypes RA and RARS. Myeloproliferative diseases showed an average of three CD34+ cells/HPF. However, the average number of CD34+ cells was significantly higher (p < 0.05) in the myelodysplastic syndrome subtypes RAEB and RAEB-T (8.7/HPF) and in acute leukaemia (including both myeloid and lymphoblastic leukaemia; 111.7/HPF). CONCLUSIONS–QBEND10 is of value for the identification of RAEB and RAEB-T in routinely processed bone marrow biopsy specimens because it enables the detection of even small increases in the number of CD34+ cells.